α-АМИНОНИТРИЛЛАР АСОСИДА ГЕТЕРОЦИКЛИК БИРИКМАЛАР СИНТЕЗИ - Кодиров , Абдуахад (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
The article provides preliminary information on the use of α-aminonitriles in organic synthesis, especially in the synthesis of heterocyclic compounds. Catalysts used in their synthesis and their types, as well as information on their effect on the yield of the reaction product, are presented. Also, information on the use of cyanohydrins of various aldehydes as cyanizing reagents is given.